Cover Picture: Metal‐Free Addition/Head‐to‐Tail Polymerization of Transient Phosphinoboranes, RPH‐BH2: A Route to Poly(alkylphosphinoboranes) (Angew. Chem. Int. Ed. 46/2015). Issue 46 (30th September 2015) - Marquardt, Christian; Jurca, Titel; Schwan, Karl‐Christian; Stauber, Andreas; Virovets, Alexander V.; Whittell, George R.; Manners, Ian; Scheer, Manfred
Abstract : High‐molar‐mass poly(alkylphosphinoboranes) are currently not accessible by conventional metal‐catalyzed dehydropolymerization. However, the mild thermolysis of a Lewis base stabilized phosphinoborane is an alternative metal‐free approach. In their Communication onpage 13782 ff., M. Scheer, I. Manners, and co‐workers describe their successful synthesis of poly( tert ‐butylphosphinoborane) by this promising strategy.